Global, regional, and national epidemiology of otitis media in children from 1990 to 2021 - Wang, HanYu; Zeng, XiaoYu; Miao, Xin; Yang, BoWen; Zhang, ShiPeng; Fu, QinWei; Zhang, QinXiu; Tang, Mi (Frontiers in Pediatrics, 2025)
BackgroundOtitis media(OM) is a prevalent ear condition, particularly among children, with a significant impact on quality of life. This study aimed to elucidate the global prevalence and disability-adjusted life years (DALYs) associated with OM in the 0–14 age group from 1990–2021, using data from the 2021 Global Burden of Disease (GBD) study.MethodsOur study conducted a comprehensive analysis of OM data from the GBD 2021 report, examining the prevalence and DALYs related to OM across 204 countries and territories over a 32-year period. Data were stratified by age, sex, year, geographic region, and sociodemographic index (SDI). Temporal trends were evaluated using estimated annual percent change (EAPC) calculations. Additionally, a global risk attribution analysis for childhood OM was conducted, and a Bayesian age-period-cohort (BAPC) model was applied to project the global burden of childhood OM from 2021–2035.ResultsIn 2021, the global burden of OM in children remained significant, with an incidence of 297,243,470 cases and an age-standardized prevalence of 14,775 cases per 100,000 population. OM resulted in 1,035,749 DALYs globally, with an age-standardized DALY rate of 51.48 per 100,000 population. Regionally, the highest age-standardized prevalence of OM was observed in Eastern Sub-Saharan Africa, South Asia, and Western Sub-Saharan Africa, while Central Europe, East Asia, and High-income Asia Pacific exhibited the lowest prevalence. Key risk factors identified include secondhand smoke, particulate matter pollution, low birth weight, and short gestation. Additionally, a significant inverse association was found between the SDI and the burden of OM, with age-standardized DALY rates decreasing markedly as SDI increased.ConclusionOM in children represents an escalating global health challenge, marked by a rising incidence. Although there has been a global decline in DALYs, the burden of DALYs associated with OM in children remains significant, particularly in regions with a low SDI. A more comprehensive understanding of the epidemiology of OM in children could enhance prevention and control efforts.